2003
DOI: 10.1097/00005176-200311000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Age and Family History at Presentation of Pediatric Inflammatory Bowel Disease

Abstract: Except for higher platelet counts, a lower BMI, and a higher frequency of positive family history in young children with CD, there were no significant differences in the presentation of young children with IBD compared with older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
4
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 28 publications
6
40
4
3
Order By: Relevance
“…Although our sample size was too small to permit definitive conclusions to be drawn, this is higher than frequencies seen in Korean adults (2.7% [14] and 1.9% [27]) and is similar to the 6.0% of children and 2.8% of adults with relevant histories reported from Japan [28]. In Western studies, the incidence of relevant family history in pediatric patients was higher (25-33%) than in our study [29,30].…”
Section: Discussionsupporting
confidence: 61%
“…Although our sample size was too small to permit definitive conclusions to be drawn, this is higher than frequencies seen in Korean adults (2.7% [14] and 1.9% [27]) and is similar to the 6.0% of children and 2.8% of adults with relevant histories reported from Japan [28]. In Western studies, the incidence of relevant family history in pediatric patients was higher (25-33%) than in our study [29,30].…”
Section: Discussionsupporting
confidence: 61%
“…(28) Hsiao et al, who looked for common mutations in the NOD2/CARD15 and TLR4 genes, which are strongly associated with CD among Caucasian patients, was unable to find any such mutations in Taiwanese children with CD. (22) This may indicate the existence of different genetic influences that are specific to the development of IBD in Asian children.…”
Section: Discussionmentioning
confidence: 99%
“…Early historical studies have suggested that the phenotypic clinical expression of Crohn's disease differs substantially, depending on the age of initial diagnosis [16][17][18][19][20] . This agedependent phenotypic clinical expression probably reflects the dynamic nature of the disorder [21] .…”
Section: Age-related Phenotypic Expressionmentioning
confidence: 99%